2017
DOI: 10.1080/14756366.2017.1347165
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study on the inhibition of xanthine oxidase by acylated derivatives of flavonoids synthesised enzymatically

Abstract: Studies have reported that flavonoids inhibit xanthine oxidase (XO) activity; however, poor solubility and stability in lipophilic media limit their bioavailability and applications. This study evaluated the kinetic parameters of XO inhibition and partition coefficients of flavonoid esters biosynthesised from hesperidin, naringin, and rutin via enzymatic acylation with hexanoic, octanoic, decanoic, lauric, and oleic acids catalysed by Candida antarctica lipase B (CALB). Quantitative determination by ultra-high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Generally, the polyphenols has been indicated to inhibit XO in a competitive manner through binding to the active site of the enzyme, of which the inhibiting activities are directly proportional to their concentrations (de Araújo et al, 2017;Ren et al, 2019). Besides, it has also been revealed that some polyphenols inhibit XO in a noncompetitive or mixed way, which means that the molecular interactions may occur both in the active site of XO and the region around the molybdopterin cofactor (Honda et al, 2017).…”
Section: Advances In Inhibition Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the polyphenols has been indicated to inhibit XO in a competitive manner through binding to the active site of the enzyme, of which the inhibiting activities are directly proportional to their concentrations (de Araújo et al, 2017;Ren et al, 2019). Besides, it has also been revealed that some polyphenols inhibit XO in a noncompetitive or mixed way, which means that the molecular interactions may occur both in the active site of XO and the region around the molybdopterin cofactor (Honda et al, 2017).…”
Section: Advances In Inhibition Mechanismsmentioning
confidence: 99%
“…The mechanism study usually depends on the kinetic and thermodynamics of the inhibition process, characterization of the conformation change of XO, and molecular docking study for simulating the interaction between the enzyme and substrate (Xiao, Kai, Yamamoto, & Chen, 2013; Xiao, Ni, Kai, & Chen, 2013; Xiao, Ni, Kai, & Chen, 2015). Generally, the polyphenols has been indicated to inhibit XO in a competitive manner through binding to the active site of the enzyme, of which the inhibiting activities are directly proportional to their concentrations (de Araújo et al., 2017; Ren et al., 2019). Besides, it has also been revealed that some polyphenols inhibit XO in a noncompetitive or mixed way, which means that the molecular interactions may occur both in the active site of XO and the region around the molybdopterin cofactor (Honda et al., 2017).…”
Section: Advances In Inhibition Mechanismsmentioning
confidence: 99%
“…It could be seen through the plots that the mode of XO inhibition by piceatannol is competitive type and the modes of XO inhibition by rhaponiticin, resveratrol, and isorhapontigenin are uncompetitive type. The competitive inhibition means the Michaelis-Menten constant ( K m ) was increasing and the maximum reaction velocity ( V max ) remained unchanged, which indicates the occupation by inhibitor prevents substrate from connecting to the active site of enzyme [18]. The uncompetitive inhibition means both K m and V max are decreased, which indicates the inhibitor caused the inhibition by forming enzyme-substrate complex reversibly with weak interactions at a site other than the active site [19].…”
Section: Resultsmentioning
confidence: 99%
“…Xanthine oxidase plays a crucial role in many drug metabolic processes, such as thiopurine drugs, containing 6-mercaptopurine, allopurinol, and uric acid, etc. [26,27,28,29]. Xanthine oxidase is important in gout patients, because XO produces uric acid, which is a crucial factor in gout.…”
Section: Discussionmentioning
confidence: 99%